Localised muscle tissue oxygenation during dynamic exercise with whole body vibration - Robbins, Daniel; Elwell, Clare; Jimenez, Alfonso; Goss-Sampson, Mark (Journal of sports science & medicine, 2012)
Despite increasing use of whole body vibration during exercise an understanding of the exact role of vibration and the supporting physiological mechanisms is still limited. An important aspect of exercise analysis is the utilisation of oxygen, however, there have been limited studies considering tissue oxygenation parameters, particularly during dynamic whole body vibration (WBV) exercise. The aim of this study was to determine the effect of adding WBV during heel raise exercises and assessing changes in tissue oxygenation parameters of the lateral gastrocnemius using Near Infra Red Spectroscopy (NIRS). Twenty healthy subjects completed ten alternating sets of 15 heel raises (vibration vs. no vibration). Synchronous oxygenation and motion data were captured prior to exercise to determine baseline levels, for the duration of the exercise and 20 sec post exercise for the recovery period. Both vibration and no vibration conditions elicited a characteristic increase in deoxyhaemoglobin and decreases in oxyhaemoglobin, total haemoglobin, tissue oxygenation index and normalised tissue haemoglobin index which are indicative of local tissue hypoxia. However, the addition of vibration elicited significantly lower (p < 0. 001) depletions in oxyhaemoglobin, total haemoglobin, normalised tissue haemoglobin index but no significant differences in deoxyhaemoglobin. These findings suggest that addition of vibration to exercise does not increase the cost of the exercise for the lateral gastrocnemius muscle, but does decrease the reduction in local muscle oxygenation parameters, potentially resulting from increased blood flow to the calf or a vasospastic response in the feet. However, further studies are needed to establish the mechanisms underlying these findings. Key pointsWhole body vibration affects tissue oxygenation of the lateral gastrocnemius.The underlying mechanism could be either increased blood flow or a vasospastic response in the feet.The local metabolic cost of heel raise activity on the lateral gastrocnemius does not appear to be increased by whole body vibration.